2012
DOI: 10.1177/0194599812447776
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Postoperative Course of Oral Prednisone on Postoperative Morbidity following Childhood Tonsillectomy

Abstract: There is no evidence of benefit from postoperative administration of corticosteroids in pediatric patients recovering from tonsillectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
3
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 14 publications
2
21
3
1
Order By: Relevance
“…Prednisolone was replaced by ibuprofen in the second part of the study. One reason was the weak impact of prednisolone on pain scores and PONV after tonsillectomy [4,5]. Indeed, one study found comparable pain scores between placebo and prednisolone administered during 7 days after tonsillectomy, with only a reduction in nausea after POD4 [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prednisolone was replaced by ibuprofen in the second part of the study. One reason was the weak impact of prednisolone on pain scores and PONV after tonsillectomy [4,5]. Indeed, one study found comparable pain scores between placebo and prednisolone administered during 7 days after tonsillectomy, with only a reduction in nausea after POD4 [4].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one study found comparable pain scores between placebo and prednisolone administered during 7 days after tonsillectomy, with only a reduction in nausea after POD4 [4]. Recently, a placebo-controlled study did not evidence any difference in pain scores, feeding and PONV after tonsillectomy in children [5]. Methylprednisolone at 2.5 mg/kg appeared to be non-inferior to dexamethasone at 0.5 mg/kg in a prospective study with PONV prevention as the primary outcome, with a difference of 8% [95% CI; -5% to 21%] [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palme compare dans une étude de faible puissance, la prednisolone à un placebo administrés pendant 7 jours après amygdalectomie ; il retrouve un effet limité de la prednisolone sur les nausées, vomissements et les scores de douleur (versus placebo) [35] (niveau de preuve 2). En 2012, Macassey montre que, comparée à un placebo, l'utilisation de prednisolone en adjonction d'un traitement antalgique standard (paracétamol, codéine, ibuprofène) ne modifie pas le profil de douleur ou de vomissements chez des enfants après amygdalectomie [36] (niveau de preuve 2).…”
Section: Ratio Bénéfice-risque Des Corticoïdes Par Voie Oraleunclassified
“…They based these recommendations on randomized studies showing that systemic formulations of steroids have been proven to reduce pain, decrease time to oral liquid ingestion, and decrease nausea . Given the effectiveness of perioperative dosing, a course of postoperative steroids has been shown in at least two studies to be a means to improve post‐tonsillectomy outcomes, whereas another study has reported no significant improvement in postoperative outcomes with steroid use . Given the conflicting nature of previous reports, we sought to examine the effect of a postoperative steroid course on post‐tonsillectomy outcomes, with a specific focus on returns to the ED for pain or bleeding, post‐tonsillectomy hemorrhage rates in the first 30 days after surgery, and phone calls to the otolaryngologists office representing an unplanned physician contact.…”
Section: Introductionmentioning
confidence: 99%